2020
DOI: 10.1016/j.cca.2020.04.026
|View full text |Cite
|
Sign up to set email alerts
|

IgA-Ab response to spike glycoprotein of SARS-CoV-2 in patients with COVID-19: A longitudinal study

Abstract: Validation studies of serological antibody tests must be properly designed for clinical, epidemiological and Public Health objectives such as confirmation of suspected COVID-19 cases, certification of seroconversion after infection, and epidemiological surveillance. We evaluated the kinetics of IgM, IgA and IgG SARS-CoV-2 antibodies in COVID-19 patients with confirmed (rRT-PCR) infection. We found that the IgA response appears and grows early, peaks at week 3, and it is stronger and more persistent than the Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
288
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(327 citation statements)
references
References 9 publications
30
288
1
8
Order By: Relevance
“…Andrea et al . [19] found that the IgA response appears early, peaks at week 3 and it is stronger and more persistent than the IgM response, which was similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Andrea et al . [19] found that the IgA response appears early, peaks at week 3 and it is stronger and more persistent than the IgM response, which was similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Serum IgA antibody responses may be detectable earlier than IgG and IgM responses1617 and can persist for at least 38 days in hospital patients recovering from covid-19 18. This is consistent with a recent Cochrane review, which found that IgA based serological testing had greater sensitivity than other methods 5.…”
Section: Look For Igasupporting
confidence: 83%
“…16,19,51,53 Another report determined earlier IgA seroconversion than IgM 54 or that IgA is detected at higher levels than IgM. 55 IgG antibodies become detectable later in the infection course around 7-14 days after symptom onset and levels remained relatively high until 6 weeks. 51,52 Although the data remain premature, a small study of 285 patients with COVID-19 reported that 100% of patients tested positive for IgG within 20 days after symptom onset.…”
Section: Serology Testingmentioning
confidence: 99%